Embassy and Consular archives (Records of the Public Record Office., 1984)
Contains miscellanea from the British consulates in Brazil, 1820-1885. Comprises dispatches, drafts and miscellaneous papers relating to the slave trade, commercial treaty negotiations, 1842 to 1845, and a special mission to the river Plate, 1847; and other papers, accounts, etc.